Neutrophil gelatinase-associated lipocalin (NGAL) in heart transplant recipients after conversion to everolimus therapy. Issue 4 (October 2015) - Stypmann, Jörg; Fobker, Manfred; Rosing, Katharina; Engelen, Markus; Gunia, Stefan; Dell'Aquila, Angelo Maria; Nofer, Jerzy-Roch
Abstract Background Due to the lack of nephrotoxic activity, proliferation signal inhibitors (PSI) such as everolimus are recommended for immunosuppression after heart transplantation, but the assessment of renal function in patients receiving PSI has led to conflicting results. We examined renal integrity and function using neutrophil gelatinase-associated lipocalin (NGAL) and conventional markers [plasma creatinine, cystatin C, urine albumin, α1-microglobulin (α1M)] in heart transplant patients, who underwent conversion to everolimus due to allograft vasculopathy, graft rejection episodes, or renal function deterioration, and in patients maintained on calcineurin inhibitors (CNI). Methods This cross-sectional study included 121 consecutive heart transplant recipients: 44 patients received CNI-free immunosuppressive therapy with everolimus and 77 patients received CNI. Renal parameters were determined in plasma and urine samples using standard enzymatic or immunochemical methods. Results Heart transplant recipients receiving everolimus therapy had significantly lower NGAL concentrations in plasma [median (95% CI): 128 (97–176) ng/mL vs. 252 (224–283) ng/mL, p < 0.001] and urine [median (95% CI): 6.4 (4.5–7.6) ng/g vs. 15.7 (10.2–25.9) ng/g creatinine, p < 0.001]. In contrast, no significant differences were observed between everolimus- and CNI-treated groups with regard to creatinine and cystatin C, as well as urine albumin and α1M levels. Significant correlations were noted between plasma NGAL and creatinine (r = 0.42, p < 0.001), cystatin C (r = 0.44, p < 0.001), N-terminal brain natriuretic propeptide (r = 0.31, p < 0.01) and indicators of chronic inflammation [lipoprotein-associated phospholipase A2 (Lp-PLA2), r = 0.31, p < 0.01] and soluble CD40 ligand (sCD40L, r = 0.22, p < 0.05), and between urinary NGAL and α1M (r = 0.21, p < 0.05). Multiple regression analysis indicated that cystatin C and Lp-PLA2 were the best predictors of plasma NGAL. Conclusion The present study documents reduced plasma and urinary NGAL levels in the absence of differences in conventional renal parameters in patients on CNI-free immunosuppressive therapy with everolimus. These results support favorable effects of everolimus on renal integrity in heart transplant recipients.